Exploring Drug Targets in Isoprenoid Biosynthetic Pathway for Plasmodium falciparum - Tabish Qidwai; Farrukh Jamal; Mohd Y. Khan; Bechan Sharma (Biochemistry Research International)
Emergence of rapid drug resistance to existing antimalarial drugs in Plasmodium falciparum has created the need for prediction of novel targets as well as leads derived from original molecules with improved activity against a validated drug target. The malaria parasite has a plant plastid-like apicoplast. To overcome the problem of falciparum malaria, the metabolic pathways in parasite apicoplast have been used as antimalarial drug targets. Among several pathways in apicoplast, isoprenoid biosynthesis is one of the important pathways for parasite as its multiplication in human erythrocytes requires isoprenoids. Therefore targeting this pathway and exploring leads with improved activity is a highly attractive approach. This report has explored progress towards the study of proteins and inhibitors of isoprenoid biosynthesis pathway. For more comprehensive analysis, antimalarial drug-protein interaction has been covered.